Thiol-/thioether-functionalized porous organic polymers for simultaneous removal of mercury(ii) ion and aromatic pollutants in water. (3rd May 2019) - Cheng, Jincheng; Li, Yifan; Li, Li; Lu, Pengpeng; Wang, Qiang; He, Chiyang
Abstract : Two novel thiol-/thioether-functionalized porous organic polymers were prepared for simultaneous removal of Hg(ii ) and aromatic pollutants in water with high binding ability and fast uptake kinetics. Abstract : The purpose of this work is to prepare effective adsorbents for simultaneously removing Hg(ii ) ion and aromatic pollutants in water, which still remains a great challenge presently due to their different physicochemical properties. Herein, two new thiol-/thioether-functionalized porous organic polymers were prepared and characterized by scanning electron microscopy, infrared spectra, 13 C CP/MAS nuclear magnetic resonance spectra, energy-dispersive X-ray spectroscopy, elemental analysis, thermo-gravimetric analysis, and nitrogen adsorption–desorption isotherms. The results showed that the two adsorbents had a loosely porous structure, high BET surface area, and good thermal and chemical stability. The optimal pH value for the two new adsorbents to uptake Hg(ii ) was 3–4. The new adsorbents presented a high adsorption ability with the maximum adsorption capacity of 180 mg g −1 for Hg(ii ) and 358–452 mg g −1 for aromatic pollutants (toluene and m -xylene as models) and acceptable/fast binding kinetics for Hg(ii ) and aromatic pollutants, respectively. The adsorbents also showed high adsorption selectivity for Hg(ii ) in the presence of commonly coexisting metal ions. Moreover, the two adsorbents had good simultaneous removal ability for Hg(ii ) and the aromatic pollutants at different concentrations and good reusability. Finally, the two new adsorbents were used successfully for the simultaneous and highly efficient removal of Hg(ii ) ion and aromatic pollutants in simulated sewage with removal efficiencies higher than 88% for Hg(ii ) and higher than 93% for the aromatic pollutants (10 mg of adsorbent mixed with 10 mL of sewage containing Hg(ii ) and the aromatic pollutants at 10 μg mL −1 for each one), indicating their great potential to be applied for the simultaneous removal of Hg(ii ) and aromatic pollutants in real sewage or wastewater.